Neurolymphomatosis as primary presentation of extra-nodal NK/T-cell lymphoma, nasal type - Silva, MI (2024)
Neurolymphomatosis (NL) describes an infiltration of cranial and peripheral nerves by lymphoma cells, most frequently in non-Hodgkin B-cell lymphoma. This clinical entity is rare and poses a challenging diagnosis. We describe a case of a 64-year-old female patient with NL associated with extra-nodal NK/T-cell lymphoma (ENKTL), nasal type, presenting as a painful progressive mononeuropathy multiplex with an oral cavity lesion. ENKTL is usually associated with Epstein-Barr virus (EBV) infection and rarely affects the central and peripheral nervous system. Lumbar puncture, magnetic resonance imaging (MRI), nerve biopsy, and 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) help to establish the diagnosis. Thereby, NL should be considered in the differential diagnosis of painful progressive multiple neuropathies, even in patients without previous history of cancer.